The Effectiveness of AI Feedback on Genre-Based Writing Skills of EFL Students - Wiki Tedi Rahmawati; Yunita Mutiara Haharap (EXCELLENCE: Journal of English and English Education, 2026)
This study investigates the effectiveness of QuillBot, a free AI feedback application, in enhancing genre-based writing skills among EFL students. Using a one-group pre-test post-test quasi-experimental design, ten first-semester students participated in writing tasks before and after receiving AI feedback. Quantitative analysis revealed a significant improvement, with mean scores increasing by 20 points (t = 12.45, p < 0.001, Cohen’s d = 2.5). QuillBot feedback reports indicated that grammar accuracy, lexical choice, and cohesion were the most improved aspects, while organization of ideas still required lecturer guidance. The findings confirm that AI feedback can serve as effective digital scaffolding in genre-based writing pedagogy.